Bacteremia, without Endocarditis, due to Streptococcus gallolyticus Subspecies gallolyticus in an Infant with Tetralogy of Fallot - Rizzo, Viviana; Di Caprio, Giovanni; Carannante, Novella; Rescigno, Carolina; Rossi, Marco; Bernardo, Mariano; Cuccurullo, Susanna; Tascini, Carlo (Journal of Pediatric Infectious Diseases, 2019)
Streptococcus gallolyticus subspecies gallolyticus (SGSG) is a rare cause of bacteremia in infants. We are reporting a case of bacteremia without endocarditis in a patient affected by tetralogy of Fallot. In the suspect of cerebral involvement, a brain image study might be useful to rule out brain abscesses or embolism. When antibiotic treatment is promptly started, prognosis is good, even with only 2 weeks of effective antibiotic therapy.
Keywords: sepsis; S. bovis; infant